2008
DOI: 10.1002/nau.20555
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence and pelvic organ prolapse in parous/nulliparous pairs of identical twins

Abstract: All four pairs of identical twins were diagnosed with identical continence status. Three pairs were identical with regard to support in all three compartments. Vaginal delivery was not associated with urinary incontinence or clinically relevant differences in relaxation of the pelvic support system within four sets of postmenopausal identical twins with different parity status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
9
0
4
Order By: Relevance
“…Evidence in the literature supports an association between paediatric and adult lower urinary tract dysfunction. Genetic as well as environmental factors have been proposed to explain this .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the literature supports an association between paediatric and adult lower urinary tract dysfunction. Genetic as well as environmental factors have been proposed to explain this .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that about a third of women have UI after childbirth [Hallock and Handa, ]. In addition to parity, a positive family history of prolapse increases a woman's risk of prolapse, even among nulliparous women [Buchsbaum et al, ; Buchsbaum and Duecy, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…In relation to collagen, joint hypermobility and various collagen diseases such as Ehlers-Danlos or Marfan syndrome are linked with POP [16]. All these factors are indicative of the systemic manifestation of collagen abnormalities and suggest a role for congenital predisposition in POP etiology [17,18]. POP is not a condition caused by pregnancy alone; it could be a clinical manifestation of a preexisting, undiagnosed condition or a congenital predisposition triggered by pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 99%